Managing for the future can the town meeting go to sea ? - Conover, David ([S.l.] : Compass Light Documentary Production [production company] ; California : The Video Project [distributor], 1998)
This program shows the experiments in local co-management fishery by both scientists and harvesters in Maine
Editor, David Conover ; executive producer, Philip Conkling, Don Perkins
Narrator: Lou McNally
Keywords: Fishery management -- New England; Fisheries